Pengaruh Disiplin Kerja Terhadap Kinerja Guru PAUD - Ruswati, Tri; Murniati, Ngurah Ayu Nyoman; Miyono, Noor (Universitas Muria Kudus, 2022)
This study aims to determine whether there is an effect of Work Discipline on PAUD Teacher Performance in Bandungan Raya District, Semarang Regency. The population in this study were PAUD teachers in Bandungan Raya Sub-district, Semarang Regency with a total of 167 PAUD teachers, which then obtained samples using proportional random sampling technique using the formula from Slovin as many as 118 people. The data analysis used was descriptive analysis, prerequisite test and simple regression analysis which was processed using IBM SPSS Statistic 23. The results showed that there was a positive and significant effect of work discipline on the performance of PAUD teachers in Bandungan Raya District, Semarang Regency, this was evidenced by the correlation between work discipline variables on performance is positive, with a calculated r value of 0.505 with Sig (2-tailed) i.e. 0.000 0.05. Furthermore, the value of R square is 0.255 = 25.5%, which means that the magnitude of the influence of the variable X2 on Y is 25.5% and the magnitude of other influences outside of work discipline that affect the performance of PAUD teachers in Bandungan Raya District, Semarang Regency is equal to 74.5%. Furthermore, it is known that the value of t arithmetic is 6.305 t table (1.658). This means that there is an influence of work discipline on performance, so the hypothesis which states there is an influence of work discipline on PAUD teachers in Bandungan Raya District, Semarang Regency is declared accepted